Pengaruh Pupuk Organik dan Anorganik terhadap Pertumbuhan dan Hasil Tanaman Sawi Hijau (Brassica rapa. L) - SIMANULLANG, ARJUNA YOHANNES; KARTINI, NI LUH; KESUMADEWI, ANAK AGUNG ISTRI (Agrotrop : Journal on Agriculture Science; Vol 9 No 2 (2019), 2019)
The Effect of Organic and Inorganic Fertilizers on The Growth and Results of Green Mustard (Brassica rapa L.). Green mustard (Brassica rapa L.) is a vegetable that preferred by many consumers, this causes many farmers cultivate this vegetables. One of the important factor in the cultivation of green mustard is fertilizer type. Alternative to improve soil quality and fertility is by providing organic matter. A field research was conducted to evaluate the effect of organic and inorganic fertilizers on the growth and yield of green mustard, in Banjar Taman Tande, Baturiti Village, Bedugul from April to June 2018. This study was designed with a Randomized Block Design with nested patterns consisting of two factors. The first factor was the type of fertilizer, which was consisted of four types of organic fertilizer, namely: vermicompost, cow manure, chicken manure, goat manure and inorganic fertilizers (NPK Mutiara). The second factor was fertilizer dosage, which was consisted of three levels, namely: 0 tons/ha, 15 tons/ha, and 30 tons/ha, while for NPK Mutiara fertilizer dosages, namely: 0 kg/ha, 150 kg/ha, and 300 kg/ha.The results showed that the effect of organic and inorganic fertilizers were not significantly different on the growth and yield of green mustard plants and RAE values. The total N content of soil on vermicompost treatment was 0.23% equal to NPK Mutiara. The total population of soil microbes on vermicompost treatment under dosage of 15 tons/ha and 30 tons/ha were 1.4 x 106 cfu/g that was much higher compared to NPK Mutiara 150 kg/ha fertilizer (0.3 x 106 cfu/g).